Waktu Ikat Adukan Beton dengan Pocket Penetrometer serta Korelasinya terhadap Nilai Slump - Narayudha, Moga; Han, Ay Lie (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
Workability of concrete mixtures has direct impact to placing, compaction and density of hardened concrete.  To date the concrete industry has mandated the slump-value obtained by the Abrams-Harder method as the standard for evaluating concrete’s workability.  On the other hand, setting time of cement strongly influences the workability of mixtures.  A slump value of zero was identified as to be the initial setting time of mixture.  Research performed at the Material and Construction Laboratory, Diponegoro University, showed that actual setting time measured by mixture testing with the Pocket Penetrometer deviates significantly from the results of the Abrams test. Further, the effect of retarding admixtures to the workability of concrete mixtures, are evaluated.Keywords: Concrete mixture, Initial setting time, Pocket Penetrometer, Slump, AbramsPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3922[How to cite: Narayudha, M. dan Han, A.L., 2005, Waktu Ikat Adukan Beton dengan Pocket Penetrometer serta Korelasinya terhadap Nilai Slump, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 3, pp. 67-74]